1993
DOI: 10.5357/koubyou.60.199
|View full text |Cite
|
Sign up to set email alerts
|

Change in Trigeminal Mesencephalic Neurons after Teeth Extraction in Guinea Pig.

Abstract: Trigeminal mesencephalic (Mes V) neurons innervating the periodontal mechanoreceptor ( PMR) are known to play an important role in controlling the bite force and jaw-movements during mastication.After teeth loss, the PMR disappears due to loss of the periodontal membrane. The present work is a study on whether cell death is induced in the Mes V neurons in association with teeth loss. The upper and lower incisors were extracted on the right side in 5 guinea pigs (extraction group) and the other 5 guinea pigs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…20 Aoki et al 21 reported that feeding a soft diet inhibited cell proliferation in the dentate gyrus of the rat hippocampus. Kimoto et al 22 conducted a morphological study in rats and proved that tooth loss caused not only receptor loss but also neuro-nal death in the mesencephalic nucleus of the trigeminal nerve. In the present study, molars were extracted from relatively young rats in the EXT group; the rats in this group must have received reduced sensory input from the periodontal membrane to the central nervous system.…”
Section: Changes In Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Aoki et al 21 reported that feeding a soft diet inhibited cell proliferation in the dentate gyrus of the rat hippocampus. Kimoto et al 22 conducted a morphological study in rats and proved that tooth loss caused not only receptor loss but also neuro-nal death in the mesencephalic nucleus of the trigeminal nerve. In the present study, molars were extracted from relatively young rats in the EXT group; the rats in this group must have received reduced sensory input from the periodontal membrane to the central nervous system.…”
Section: Changes In Body Weightmentioning
confidence: 99%
“…24,25 In addition, reduced information input has been shown to induce neuronal death, 26 suggesting a reduced population of hippocampal pyramidal cells. Tooth loss appeared to not only cause the death of the neurons in the mesencephalic nucleus of the trigeminus 22 but also induce hippocampal dysfunction, thus impeding learning and memory.…”
Section: Changes In Body Weightmentioning
confidence: 99%